Are foreigners the vectors of Contagion? A study of six emerging markets (2018)
We investigate for the role of Foreigners, Local Institutions and Local individuals in days of Contagion in a set of six emerging markets from 2007 to 2016. We propose a new and intuitive continuous measure of Contagion based on the probability of a coincidence of daily negative returns in both the S&P500 and the local index, in excess of what can be explained by fundamentals. Using a VAR setting, we find that Foreigners sells induce Contagion, and that they keep selling in the following days. We also find evidence of Foreigners acting as the transmitters of large drops in the US stock market to emerging ones. Institutions also contribute to Contagion days with net sales, but they become net buyers from the day after. Finally, individuals are net buyers in Contagion days.